Ambition on unstable foundations: The UK Trade Policy Readiness Assessment 2020 - David Henig (European Centre for International Political Economy (ECIPE), 2020)
The UK's road to an independent trade policy has reached a critical moment. Within the next six months Free Trade Agreements (FTAs) containing long term arrangements and rules could be finalised with the United States and / or European Union, who between them constitute around 65% of UK trade. Talks have also started with Japan, Australia, and New Zealand. Our updated Trade Policy Readiness Assessment suggests that the UK government is not fully ready for this activity. On a scale where 1 suggests no work being undertaken, 3 a stable position to begin talks, and 5 successful delivery, we find problems in seeking consensus, expanding priorities beyond the traditional tariff reduction, and putting in place a realistic implementation plan.
Keywords: 330